Sub 10-nm Pd Nanocubes and Their Coating with Multi-Armed Pt Shells: Facile Synthesis and Catalysis of Alkaline Oxygen Reduction. Issue 8 (13th May 2015) - Yang, Chia-Chen; Chen, Ho-Rei; Lee, Chien-Liang
Abstract : Pd nanocubes (∼10 nm) and Pd nanocubes coated with multi-armed Pt shells have been successfully prepared. Their microstructures are determined from their electron diffraction patterns and line scan energy-dispersive X-ray measurements taken on a single particle. These Pd nanocubes and the Pd-Pt nanocubes are applicable as catalysts for the alkaline oxygen reduction reaction. On the basis of the same loading mass of catalyst, the results of rotating ring-disk electrode measurements indicate that the cubic Pd nanoparticles and particles coated by multi-armed Pt shells display activities of 1.47 × 10 −2 and 9.22 × 10 −3 mA μg −1, respectively. These values are greater than the 6.79 × 10 −3 mA μg −1 observed for Pt nanoparticles. The prepared Pd nanocubes and the Pd-Pt core-shell catalysts, as well as Pt nanoparticles, show 98% efficiency in the production of OH − via an approximate four-electron pathway. Additionally, a fair comparison supported by transmission electron microscopy and electrochemical data shows that the shapes of Pd nanocubes coated with multi-armed Pt shells are nearly unchanged by the ORR and that these core-shell catalysts show stabilities superior to Pd nanocubes.